Effectiveness of modisco supplementation in improving weight and height of stunted children: A quasi-experimental - Siti Maryati; Budi Punjastuti; Laily Mualifah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2026)
Background: Stunting continues to pose a significant public health challenge in Indonesia, particularly in regions such as Pajangan, Bantul Regency. The condition stems not only from poverty but also from inadequate dietary practices and a lack of nutritional awareness. The Modified Diet Skim Milk Sugar Cotton Seed (Modisco) formula presents a viable alternative for stunted toddlers.   Objectives: This study aimed to assess the impact of Modisco, a high-calorie oral supplement, on improving the weight and height of stunted toddlers. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted involving 20 stunted children aged 2 to 5 years, selected using purposive sampling. Participants were evenly divided into two groups an intervention group that received daily Modisco supplementation for 14 days, and a control group that did not receive any treatment. Results: The Modisco intervention produced significant improvements in both weight and height among stunted toddlers. The intervention group gained an average of 0.48 kg, while the control group showed no meaningful increase (p=0.004). Height improved by 1.84 cm in the intervention group, whereas the control group experienced a slight decline of 0.30 cm (p=0.001). Analyses within and between groups confirmed consistent, statistically significant changes following the 14-day supplementation. These findings indicate that Modisco effectively supports short-term nutritional recovery and promotes linear growth. Overall, the intervention demonstrated clear benefits in enhancing growth outcomes compared with the control group. Conclusions: These findings suggest that Modisco supplementation can effectively promote physical growth in stunted toddlers within a short timeframe. As such, it holds potential as a cost-effective and practical approach for stunting intervention programs at the community level.